Les zones de tolérance à Cuba sous la république : l’enfermement réel et symbolique des femmes publiques - Mélanie Moreau-Lebert (Études Caribéennes)
The republican era in Cuba is a complex and difficult one for the Cuban population. 1898 remains engraved in people’s memories as being a time of great disillusion for a population who, having freed itself from Spanish colonial domination, was deprived of independence by the United States of America. Three years of American intervention sufficed to put power bases into place, guarantee maximal exploitation conditions and organize the legal framework of the American domination over Cuba by means of the Platt Amendment in 1901. The protectorate set up by the United States, followed by a neocolonial system in 1934, relies upon the collaboration of presidents and corrupt governments succeeding each other in power. Corruption, nepotism and violence are put in place in a society in which inequality is dramatically worsening and all moral values are disintegrating. In this context and in a Cuban society governed with patriarchal rules, women are the first victims of the system. After the wars of independence, the only options they have are marriage, work or prostitution. Legitimate marriage is only available to a privileged few. With regards to employment, only 9.8% of women have the opportunity to work and this percentage didn’t change until 1959. It was at this time that prostitution reached unprecedented levels. It wasn’t just the case of a few marginalized women but of thousands of mothers, wives, widows and working women who were trapped in this alienating condition, forced to sell their bodies. Legislation and violence are used to control and restrict the work space for prostitutes, removing these ‘streetwalkers’ from the public eye, grouping them together in tolerance zones with very strict rules, which are in reality in the hands of Cuban and French procurers, and subjecting them to constant inspections carried out by hygienists who physically and symbolically assault women’s bodies. What is more, speeches about prostitution, whether made by politicians, feminists, journalists, doctors or mere observers, contribute significantly to a certain representation of these women. While debates about prostitution have recently shaken public opinion, this work refers back to an episode of Cuba’s history which brings us to reflect upon the evolution of the phenomenon and on its protean nature.